The readiness theme development from a case study in Thailand halal restaurants / Wannasiri Wannasupchue … [et al.] - Wannasupchue, Wannasiri; Mohamad, Siti Fatimah; Che Ishak, Farah Adibah; Ungku Zainal Abidin, Ungku Fatimah (Universiti Teknologi Mara Selangor, 2019)
Tourism industry in Thailand had generated a significant amount of the country’s revenue, with approximately USD54 billion in 2017. The number of tourist arrival is expected to continue to increase by 10 percent annually, which in turn would increase the revenue of the food and beverage sector. The northeastern area in Thailand is becoming popular among Muslim travelers and the demand of halal food is increasing. Nevertheless, the number of halal certified restaurants in the northeastern region is meagre to match the influx of Muslim tourists into the area. A number of restaurants in northeastern area provide halal food without a halal certificate. Restaurants with a halal logo displayed can facilitate tourists’ selection of an eating outlet. Hence, the purpose of this study is to identify, by means of a qualitative approach, the readiness of the noncertified halal restaurant towards obtaining halal certification. Semi-structure interviews were conducted with informants comprising (1) operators of halal certified restaurants (HCRs) and non-certified halal restaurants (NCHRs) and (2) the halal authority. The data was analysed using ATLAS where six themes emerged from the thematic analysis. Appropriateness, management support, change efficacy, discrepancy, personally beneficial, and perception towards change efforts were the readiness dimensions developed from this study. This study also mapped the readiness of the restaurants into six readiness stages. NCHRs were identified to be at the pre-contemplation and contemplation stages. Meanwhile, HCRs were classified to be at the maintenance and terminate stages. In addition, the findings could facilitate better understanding of the current situations and efforts that should be carried out by the authorised bodies to promote halal food in Thailand.